Characterisation of PolyVinyl Alcohol (PVA) as a water-soluble sacrificial layer for affordable surface micromachining - Jijo Mathen Varghese (2013)
Micro-Electro Mechanical Systems (MEMS) play a significant role in many industries today. These include aerospace, automotive, biomedical, optical display and wireless communication. MEMS are very small devices that can sense, think, communicate and even act. This makes them the backbone of many industries. As the sizes of these devices gets smaller and smaller to the micro- or nano-scale, the fabrication process becomes a challenge.